Skid resistance performance and texture lateral distribution within the lanes of asphalt pavements - Di Yun; Liqun Hu; Ulf Sandberg; Cheng Tang (Journal of Traffic and Transportation Engineering (English ed. Online), 2025)
The skid resistance and pavement texture can vary a lot for different lane paths, meaning that the lateral shift of the vehicle driving in the lane section can affect the safety significantly. On the other hand, a varying skid resistance across a lane section provides the opportunity to influence vehicles to run in lateral positions where the tire/road friction has not yet been reduced by wear; thus, improving safety. This measure would be useful only if the distribution of skid resistance and pavement texture in the lane sections are investigated at frequent intervals.This study focused on four test sections on in-service urban roads. A friction measuring device known as the T2GO system was used to test the skid resistance performance of pavements for both dry and wet conditions. A high-precision 3D-scanner was used to capture the pavement macrotexture, and a microscope was employed to investigate the pavement abrasion. Subsequently, the effect of the lateral variation across the lane of friction and texture was discussed. The feasibility of displacing the vehicles to run in tracks with better skid resistance was explored in terms of the measured friction and the texture-dependent drainage capacity. The results indicated that driving closer to the lanes' right side means that better values of friction, texture, and drainage parameters of the unworn pavement surface can be utilized. A 0.3 m or more lateral displacement would create improved friction, in a range between 13% and 14% for 1.5 m track width and between 8% and 11% for 1.65 m track width. Furthermore, the results are useful in studying the vehicles' sideslip.